2016
DOI: 10.1145/2897824.2925905
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dynamic skinning with low-rank helper bone controllers

Abstract: Dynamic skin deformation is vital for creating life-like characters, and its real-time computation is in great demand in interactive applications. We propose a practical method to synthesize plausible and dynamic skin deformation based on a helper bone rig. This method builds helper bone controllers for the deformations caused not only by skeleton poses but also secondary dynamics effects. We introduce a state-space model for a discrete time linear time-invariant system that efficiently maps the skeleton motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Furthermore, an animator would need to learn to use the fitted bone structure in order to author new animations. Example-based skinning methods have been developed [Feng et al 2008;Mohr and Gleicher 2003;Mukai and Kuriyama 2016;Wang et al 2007] that uses the original skeleton from a character rig. These methods use training examples to learn a deformation model that can approximate mesh deformations given new skeleton poses not seen during model training.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, an animator would need to learn to use the fitted bone structure in order to author new animations. Example-based skinning methods have been developed [Feng et al 2008;Mohr and Gleicher 2003;Mukai and Kuriyama 2016;Wang et al 2007] that uses the original skeleton from a character rig. These methods use training examples to learn a deformation model that can approximate mesh deformations given new skeleton poses not seen during model training.…”
Section: Related Workmentioning
confidence: 99%
“…Loper et al [17] showed how realistic pose and body shapes can be extracted from standard motion capture markers by using a data-driven human body model, and Tsoli et al [18] focused on capture-based modeling of breathing. Fast models for real-time applications rely on combining linear blend shapes [19], rotation regression [6] or helper-bone rigs that have proven useful for delivering effects such as muscle bulging [5,20]. Another exciting strand of current research is learning dynamics from data, either using statistical methods [21] or by combining statistical methods with physics-based simulation [22].The most recent work [22] is starting to show promise of being able to generalize to imaginary artist-designed characters.…”
Section: Related Workmentioning
confidence: 99%
“…Many techniques have been proposed to overcome this problem [McAdams et al 2011]. Larboulette et al [2005] used a simple blend between static skinning and dynamic deformation, and Mukai and Kuriyama [2016] added helper bones that add dynamic behaviors to LBS. The dimensionality reduction is an effective and principled approach for efficient simulation of deformable bodies.…”
Section: Related Workmentioning
confidence: 99%